ANALISIS IMPLEMENTASI STRATEGI PROMOSI KESEHATAN DALAM PENCEGAHAN FILARIASIS DI WILAYAH KERJA PUSKESMAS TANJUNG SENGKUANG KECAMATAN BATU AMPAR KOTA BATAM TAHUN 2019 - Dharma Trinata; Thomson P Nadapdap; Anto Anto (Jurnal Mutiara Kesehatan Masyarakat, 2019)
Filariasis is still a health threat in several regions in Indonesia. One of the government's strategies in preventing filariasis is to provide health promotion through counselling to people in endemic areas. The purpose of this study was to analyze the implementation of health promotion strategies in the prevention of filariasis. This research was a qualitative research with a descriptive approach and was conducted at Tanjung Sengkuang Health Centre. The informants were 6 people. Data were analysed with the stages of data reduction, data display, and conclusion or verification. The results showed that community empowerment was done by providing cadre training 2 months before the activity, direct counselling to the community, mobilizing the community in BELKAGA activities, motivating midwives/cadres to go to the community. The atmosphere building activities are inviting cadres to the field, establishing posts in each village, cross-sectoral collaboration, ensuring counselling schedules and taking medicine. Advocacy by putting the doctor in charge of the program approaches with elements of the community. The Partnership coordinates with heads of offices, members of the DPR, mass organizations, community and religious leaders, heads of RT/RW, youth, and companies. Supporting factors are the support of health workers, funds from the government, cadres and midwives as role models, Helath Centre infrastructure facilities, distribution of manuals, stickers and banners. The inhibiting factors are boredom, fear of side effects, the majority of workers, different catches, medical personnel are not proportional to the population and area. It is recommended to the Tanjung Sengkuang Health Centre to overcome the inhibiting factors found in the health promotion strategy for preventing filariasis